Comparative analysis of the properties of Guadua Angustifolia Kunt as an innovative and cost-effective material in structural construction - Yeisi Katherine Flórez-López; Keily Yolina Vera-Pérez; Miguel Ángel Hernández-Peña; Edinson Davey Barbosa-Burgos (Sostenibilidad, Tecnología y Humanismo, 2020)
In construction the conventional materials have been evolving with the purpose of minimizing the problem with the environment, due to this new materials are born that are being studied, a clear example of this is the bamboo, that is a material 100% natural and with great diversity in Colombia. This work analyzes and compares the properties of bamboo angustifolia Kunth as a construction material, determining some of its most favorable characteristics according to the studies carried out in Colombia, giving it an approach for its use as a structural element in addition to cataloguing it as a renewable, sustainable and nature-friendly material. The content is organized with a classification of the studies and laboratories made to the guadua angustifolia Kunth, the characteristics found from those studies and the description of the different locations of guadua in Colombia.